2014
DOI: 10.5581/1516-8484.20140010
|View full text |Cite
|
Sign up to set email alerts
|

Mannose-binding lectin 2 (MBL2) gene polymorphisms do not influence frequency of infections in chronic lymphocytic leukemia patients

Abstract: BackgroundInfectious complications represent the main cause of morbidity and mortality in chronic lymphocytic leukemia. It has been reported that polymorphisms of the mannose-binding lectin 2 (MBL2) genes are correlated with MBL protein serum levels and, consequently, are associated with the development of infectious diseases.ObjectiveThe purpose of this study was to investigate the possible association between MBL2 gene polymorphisms and risk of infection in chronic lymphocytic leukemia patients.MethodsPeriph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
1
3
1
Order By: Relevance
“…Similarly, the lack of association of mannose-binding lectin deficiency with chemotherapy-induced infections in patients suffering from acute myeloid leukaemia was earlier reported by Bergmann et al 39 and Klostergaard et al 40 . Furthermore, data from several other studies (concerning patients with other leukaemias, or haematological malignancies in general) led to similar conclusions [41][42][43][44][45][46] . In contrast to our results presented here and in afore-mentioned recent paper 37 , some earlier reports suggested that low MBL (or associated genotypes) enhanced the risk for infections in such cases 31,32,36,[47][48][49][50] .…”
Section: Aml Aml-a Aml-b Aml-c Aml-dsupporting
confidence: 62%
“…Similarly, the lack of association of mannose-binding lectin deficiency with chemotherapy-induced infections in patients suffering from acute myeloid leukaemia was earlier reported by Bergmann et al 39 and Klostergaard et al 40 . Furthermore, data from several other studies (concerning patients with other leukaemias, or haematological malignancies in general) led to similar conclusions [41][42][43][44][45][46] . In contrast to our results presented here and in afore-mentioned recent paper 37 , some earlier reports suggested that low MBL (or associated genotypes) enhanced the risk for infections in such cases 31,32,36,[47][48][49][50] .…”
Section: Aml Aml-a Aml-b Aml-c Aml-dsupporting
confidence: 62%
“…The MBL2 plays an important role in the innate immune system and few polymorphisms in this gene can be responsible for increased susceptibility to some infectious diseases [70][71][72]; therefore, MBL2 insufficiency is related to bacterial infection [73]. The present meta-analysis could not find any association between MBL2 (rs7096206 and rs1800450) polymorphisms, perhaps due to a limited number of included studies.…”
Section: Discussioncontrasting
confidence: 60%
“…Thus, MBL can recognize carbohydrate structures, on a variety of microorganisms surface [18]. In according to our findings in the gingival tissue, the MBL plasma levels have been reported to increase during infections and inflammatory processes [19]. MBL plasma concentrations were not significantly different in moderate and severe periodontitis compared to controls, and MBL deficiency was not related to susceptibility for periodontitis [20].…”
Section: Discussionmentioning
confidence: 52%